Digital Transformation in Medical Education: Trends, Challenges, and Future Directions - Deepika Velusami; Krishnamurthy Soundariya (Achievements and Challenges of Medicine and Medical Science Vol. 4, 2024)
In recent years, digital technology has profoundly transformed medical education, reshaping how students learn and engage with the field. This chapter critically examines how various digital tools, such as virtual classrooms, interactive media, and simulation technologies, have revolutionized medical training. Beyond providing an overview of these advancements, the chapter delves into the challenges associated with their implementation, including issues of accessibility, cost, and the need for faculty training. Furthermore, it explores the broader implications of these technologies on medical education, offering potential solutions and highlighting future trends that may drive further innovation. A critical analysis of the limitations and potential of digital tools provides a more nuanced understanding of their role in shaping the future of medical education.